The Effectiveness of Enterprise Resource Planning on the Performance Quality of Food Company Employees in West Java - Teddy Hikmat Fauzi; Latifah Adnani; Maun Jamaludin (Research Horizon, 2022)
Implementing Enterprise Resources Planning (ERP) in the company is part of the company's internal business strengthening strategy to increase strong competitiveness and manage the company professionally. However, implementing ERP systems in some cases is considered a failure because the company does not achieve the goals set. This study aims to determine whether the implementation of the system in the company has a positive effect on employee performance. The models used to evaluate the impact of ERP system implementation are work quantity, work quality, work knowledge, collaborative creativity, dependability, initiative, and personal quality. The method used in this research is a descriptive, analytic and evaluative qualitative method by analyzing the impact of ERP system implementation on user performance components in food companies in West Java. The results obtained are that ERP implementation positively affects work quantity, work quality, knowledge, collaboration, creativity, dependence, initiative, and personal quality.